An exploration of the factors influencing successful implementation, delivery and outcomes in an intensive care sedation study: process evaluation of the A2B RCT - Aitken, Leanne M; Emerson, Lydia M; Kydonaki, Kalliopi; Blackwood, Bronagh; Creagh-Brown, Ben; Lone, Nazir; McKenzie, Cathrine; Parker, Richard; Reade, Michael C; Weir, Christopher J; Wise, Matt P; Walsh, Timothy S (Health technology assessment (Winchester, England), 2025)
Choice of sedation of critically ill patients is a core element of intensive care practice. The alpha 2 agonists for sedation to produce better outcomes from critical illness (A2B) trial tested the effectiveness of two alpha agonist sedatives versus propofol in reducing time on mechanical ventilation in 38 intensive care units in the United Kingdom. To evaluate both how this complex trial was implemented and how this may have influenced trial outcomes, an understanding of the contextual and practice variation across multiple sites was required. The aim of this process evaluation of the A2B trial was to determine how the intervention was delivered, the extent to which it was delivered as intended and the impact this had on outcomes. Specifically, we aimed to: Establish the degree to which the A2B intervention was delivered as intended, specifically in relation to fidelity, dose and reach across patients. Understand factors that impacted on successful delivery of both the A2B intervention and trial, in relation to attitudes and perceptions of staff, including context and standard care. A mixed-methods, multiphase design was used following extensive pre-trial exploration of current practice. Quantitative data were drawn from the main trial database covering 38 sites to assess the intervention's fidelity, dose and reach in each site. Data were analysed descriptively and provided a low-moderate-high rating. Qualitative data were collected by interviews mid trial (phase 1) and end of trial (phase 2). Participants were recruited from a random sample of 30 intensive care units active at the time of sampling and included the principal investigator, research nurses and clinical staff. Semistructured interviews, informed by the trial's logic model, lasted 45-60 minutes. Data collection focused on whether the intervention could be delivered as intended, factors that impacted upon successful delivery and understanding intervention adherence. Analysis used a framework approach based on the logic model. Data collection and qualitative analyses were completed prior to knowing the primary results of the trial. Site intervention adherence ratings for fidelity, dose and reach were low (4), moderate (20) and high (14). Participants from 12 intensive care units in each of phase 1 (33 staff) and phase 2 (36 staff) provided qualitative data; participating intensive care units differed between phases. Factors identified in phase 1 focused on intervention delivery and trial conduct and incorporated both organisational and participant-related factors. In phase 2, participant-related factors included clinician preference, individual equipoise, clinician resistance and staff capability and capacity, while A2B trial-related factors included concerns relating to safety and side effects, overnight deep sedation practice, patient comfort and trial documentation. Many of these factors were impacted by the COVID-19 pandemic, particularly in regard to staffing numbers and experience. Due to the impact of the COVID-19 pandemic, most data collection occurred remotely through video-conferencing rather than planned at site observation and interviews. Optimal sedation practice is influenced by multiple factors related to clinician perceptions, capacity and capability. Priorities in care focus on short-term safety and comfort. Limitations in staffing mean that longer-term consequences related to recovery and rehabilitation are second tier considerations. Findings highlight the multiple contextual factors, including both organisational and participant-related characteristics, that should be considered when planning both clinical trials and changes to routine care. Multiple strategies for achieving behaviour change when implementing complex interventions are essential. This article presents independent research funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme as award number 16/93/01.